Prospects of Nuclear Power-Based Industry As A Replacement For Depleting Tin Resources In Bangka Belitung - Andri Yanto; Faidatul Hikmah (Badan Pengelola Usaha (BPU) Universitas Jambi, 2023)
The depletion of tin resources in Bangka Belitung poses a significant challenge for the region's economic sustainability and energy security. This study explores the prospects of establishing a nuclear power-based industry as a replacement for depleting tin resources. The research employs a comprehensive methodology that includes a literature review, data collection, potential assessment, sustainability analysis, economic implications analysis, case study, scenario analysis, and policy recommendations. The study begins with a literature review, which provides a foundation of knowledge on nuclear power technology, tin resources, and their respective industries. Data collection is then conducted to gather relevant information on the current tin production and consumption trends in Bangka Belitung, as well as data on nuclear power technology, its potential implementation, and its economic and environmental implications. The findings of this research suggest that a nuclear power-based industry holds promise as a viable alternative to address the depletion of tin resources in Bangka Belitung. The potential assessment demonstrates the feasibility of implementing nuclear power technology, while the sustainability analysis highlights the importance of addressing environmental and social concerns. The economic implications analysis reveals potential economic benefits and the case studies provide insights into possible scenarios. The policy recommendations offer guidance for sustainable development and effective stakeholder engagement.